The impact of livestock and fisheries on food availability and demand in 2020 - Delgado, Christopher L.; Crosson, Pierre; Courbois, Claude (International Food Policy Research Institute, 1997)
People in developed countries consume about 3 to 4 times as much meat and fish, and 5 to 6 times as much milk products per capita as in developing Asia and Africa. Yet, meat, milk, and fish consumption per capita has barely grown in the developed countries as a whole over the past 20 years. Growth in per capita consumption and production has occurred in developing regions such as developing Asia, where income has increased from a low level and urbanization is rapid. By 2020, according to projections by IFPRI's IMPACT model, the share of the developing countries in total world meat consumption will rise from 47 percent currently to 64 percent. The net impact on food access for the poor of the world will depend on their role as producers of meat, milk, and fish, their role as consumers, and their need for protein. The amount of cereals per capita consumed directly by rural people will decline as they diversify their diets into animal proteins, but feed use will increase greatly. Available evidence suggests that on balance poor consumers in developing countries will probably be better off.